Risk of Hepatitis B Transmission After Amniocentesis in Chronic Hepatitis B Carriers - James M. Alexander; Ronald Ramus; Gregory Jackson; Barbara Sercely; George D. Wendel (Hindawi Limited, 1999)
Objective: To measure the risk of perinatal transmission of HBV in chronic carriers who undergo amniocentesis.